Historika Supervisi Pembelajaran: Perkembangan dan Implikasinya dalam Dunia Pendidikan - Sugianto, Endrik; Roziqin, Khoirul (AHKAM, 2025)
Learning supervision has undergone significant development over time. This article examines the evolution of learning supervision and its implications in the world of education today. By using literature analysis from various articles, this research aims to understand the strategic role of supervision in improving the quality of education, facing the challenges of digital era, and improving teacher professionalism. The method used is literature study using a conventional approach. In addition, academic supervision is a major need in improving the quality of education in the digital era. Therefore, the implementation of effective supervision needs more attention in education policy.